Lovastatin-Induced Apoptosis in Prostate Stromal Cells - Sebastian J. Padayatty; Marco Marcelli; T. C. Shao; Glenn R. Cunningham (1997)
Benign prostatic hyperplasia (BPH) is a common disease of aging men. Current medical treatment for this condition is only partially effective, therefore many patients must undergo surgery for symptomatic relief. BPH is caused by an increase in prostate epithelial and stromal cells, especially the latter. Since BPH stromal cells have a long life span and are not very responsive to androgen withdrawal, cultured BPH stromal cells were used to explore the feasibility of pharmacologically inducing apoptosis in these cells. We obtained BPH tissue during surgery, and stromal cells were isolated and maintained in culture. After cells achieved confluence, we induced apoptosis with the HMGCoA reductase inhibitor, lovastatin (30μ mol/L). The effects of testosterone (100 μmol/L), dihydrotestosterone (DHT; 100 μmol/L) and finasteride (100 μmol/L) on lovastatin-induced apoptosis were studied on cells grown in media containing charcoal stripped serum. Similarly, we examined the effect of the cholesterol pathway metabolites, mevalonic acid (30 μmol/L), geranyl geraniol (30 μmol/L), farnesol (10 μmol/L), squalene (30μ mol/L) and 7-ketocholesterol (3 μmol/L) on lovastatin-induced apoptosis. We demonstrated apoptosis by DNA laddering in agarose gels, by fluorescence microscopy following acridine orange staining, and by flow cytometry after end-labeling of DNA strand breaks with biotin-16-dUTP using deoxynucleotidyl exotransferase (TdT). Lovastatin at 30 μmol/L, but not at lower concentrations, induced apoptosis in BPH prostate stromal cells. This was seen (by flow cytometry) in 16.6 ± 7.3% (mean ± sd) of BPH cells treated with lovastatin at 72 h vs. 2.5± 1.2% of cells treated with ethanol. Lovastatin-induced apoptosis was not increased in stripped serum or by the addition finasteride, and was not inhibited by testosterone or DHT. Only mevalonate and geranyl geraniol, prevented lovastatin-induced apoptosis whereas farnesol, squalene, or 7-ketocholesterol did not. We conclude that lovastatin can induce apoptosis in BPH stromal cells in vitro, and this is not affected by androgen withdrawal or stimulation. It is unlikely that lovastatin, per se, will be an effective treatment for BPH in vivo, but it does provide a means for inducing apoptosis in vitro. Understanding the apoptotic process in BPH stromal cells ultimately may lead to new therapeutic strategies for BPH.